2012
DOI: 10.1111/j.1365-2788.2012.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and alcohol‐related interventions for people with mild/moderate intellectual disabilities: a systematic review of the literature

Abstract: This review is the first to systematically collate evidence on tobacco and alcohol-related interventions for people with ID. While there is currently little evidence to guide practice, the review delivers clear insights for the development of interventions and presents a strong case for more robust research methods. In particular there is a need to test the effectiveness of interventions in large-scale, well-designed trials and to ensure that outcome measures are developed/tailored appropriately for this clien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 30 publications
2
58
0
Order By: Relevance
“…In contrast, the existing literature on adults with ID is limited in quantity and quality. In a systematic review of alcohol-related interventions, the authors found only one randomised controlled trial (RCT) evaluating educational materials about substance misuse in groups of adults with ID recruited from both community and hospital settings [10]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the existing literature on adults with ID is limited in quantity and quality. In a systematic review of alcohol-related interventions, the authors found only one randomised controlled trial (RCT) evaluating educational materials about substance misuse in groups of adults with ID recruited from both community and hospital settings [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In terms of quality, the existing studies have used uncontrolled designs, pre and post evaluations or case studies/case series and or offenders in secure hospitals who are unlikely to use any skills learned in the community [10]. None of the studies has included an evaluation of cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research thus underscores previous findings suggesting that treatment interventions for individuals with MBID must be tailored to their needs (e.g. Degenhardt 2000; Kerr et al 2013). …”
Section: Discussionmentioning
confidence: 47%
“…Burgard et al 2000;Degenhardt 2000). Thus, there is a need for more research to improve the care and treatment of individuals with MBID who have problematic substance use (Carroll Chapman and Wu 2012;Van Duijvenbode et al 2015;Kerr et al 2013).…”
Section: Introductionmentioning
confidence: 99%